The Challenges in Learning ICAO Radiotelephony: Students' Perspective - Dani Chandra Yudho Pranoto; Susanto, Fajar (Politeknik Penerbangan Indonesia Curug, 2024)
This study investigates challenges faced by Batch 13 Air Traffic Control (ATC) students at Politeknik Penerbangan Surabaya in mastering standardized ICAO Radiotelephony skills. Through qualitative methods like interviews, observations, and document analysis, the research uncovers various hurdles, from linguistic complexities to practical issues. Students struggle with English proficiency, accent variations, and applying phraseologies in real-world scenarios. The study highlights the importance of continuous practice and peer collaboration in overcoming these obstacles, emphasizing interactive pedagogy's role in fostering professional skills. By building on existing research, the thesis offers insights for aviation education enhancement, advocating tailored approaches to accommodate diverse learning needs. It calls for an inclusive learning environment to facilitate effective mastery of ICAO Radiotelephony skills.